2016
DOI: 10.1158/1078-0432.ccr-15-2052
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Immunomodulatory Interleukin-27 Enhances Oncogenic Properties of Mutant p53 In Vivo

Abstract: Purpose p53 is mutated in about 50% of human cancers, mostly through missense mutations. Expression of mutant p53 is associated with poor clinical outcomes or metastasis. Although mutant p53 is inherently instable, various stressors such as DNA damage or expression of the oncogenic Kras or c-myc affect the oncogenic properties of mutant p53. However, the effects of inflammation on mutant p53 are largely unknown. Interleukin-27 (IL-27) is an important immunomodulatory cytokine but its impact on mutant p53-drive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…One of the most critical tumor suppressors, p53, is inherently instable and mutated in approximately 50% of tumors, and various stressors such as DNA damage or oncogenic activation such as RAS mutations can affect the oncogenic properties of the mutant p53 (46). Because IL-27 possesses anti-inflammatory and antitumor properties, the role of endogenous IL-27 signaling in the mutant p53-mediated tumorigenesis was investigated (47). Lack of IL-27 signaling was shown to decrease the survival and double the incidence of osteosarcoma, possibly due to increased stability of the mutant p53 protein expression, indicating that IL-27 signaling negatively modulates the oncogenic properties of mutant p53 in vivo (47).…”
Section: Interleukin-27mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most critical tumor suppressors, p53, is inherently instable and mutated in approximately 50% of tumors, and various stressors such as DNA damage or oncogenic activation such as RAS mutations can affect the oncogenic properties of the mutant p53 (46). Because IL-27 possesses anti-inflammatory and antitumor properties, the role of endogenous IL-27 signaling in the mutant p53-mediated tumorigenesis was investigated (47). Lack of IL-27 signaling was shown to decrease the survival and double the incidence of osteosarcoma, possibly due to increased stability of the mutant p53 protein expression, indicating that IL-27 signaling negatively modulates the oncogenic properties of mutant p53 in vivo (47).…”
Section: Interleukin-27mentioning
confidence: 99%
“…Because IL-27 possesses anti-inflammatory and antitumor properties, the role of endogenous IL-27 signaling in the mutant p53-mediated tumorigenesis was investigated (47). Lack of IL-27 signaling was shown to decrease the survival and double the incidence of osteosarcoma, possibly due to increased stability of the mutant p53 protein expression, indicating that IL-27 signaling negatively modulates the oncogenic properties of mutant p53 in vivo (47). In addition, lack of IL-27 signaling was demonstrated to cause spontaneous liver inflammation, fibrosis, and steatosis (48).…”
Section: Interleukin-27mentioning
confidence: 99%
“…IL-27 is an IL-12 family cytokine that is known to inhibit autoimmune Th17 and Th2 responses (16,17). Accumulating evidence from animal studies has indicated that both endogenous (18,19) and exogenous (20)(21)(22) IL-27 inhibit tumor growth. A variety of mechanisms including enhancement of tumor-specific T cell responses (20,21) have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…A key finding of this study is the tumor promoter activity of IL27 in the skin, and this discovery is surprising given that previous studies have attributed to IL27 anti-tumor activities mainly via eliciting an anti-immune response [11] [2733]. Furthermore, in vitro studies suggest that IL27 promotes accumulation of Th1 response in keratinocytes via secretion of CXCL10 [34].…”
Section: Discussionmentioning
confidence: 93%